STRATEGI KOMUNIKASI POLITIK CALON LEGISLATIF PEREMPUAN DI KABUPATEN TABANAN TAHUN 2019 - Widiyanti, Luh Ning; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2021)
Women's representation in the political sphere has not maximized until recently. Women candidates have also adopted various political communication strategies to gain the trust and voices of the public. The purpose of this study is to determine the political communication strategies carried out by women legislative candidates in Tabanan Regency that have successfully passed the 2019 general election. This strategy is carried out by using the kinship approach, making women the main target of the campaign, utilizing social networks, using a direct communication approach or through social media, and taking psychological and sociological approaches. As a female candidate, various obstacles are faced in implementing this strategy, such as a lack of knowledge and experience regarding politics, the dual role of a woman, the public's view of a woman who is considered incapable of leading society, and competition with other candidates in one party. Keywords: Women Legislative Candidates, Political Marketing, Political Communication Strategy